Exploring the integration of medicine and sport at macro-, meso-, and microlevels of development for high athletic performance and lifelong public health with reference to practices at the University of Northern Iowa - Smith, J.; Romanazzi, F.; Smolianov, P.; Morrissette, J. N.; Dion, S.; Schoen, C.; Dolmatova, T (Journal of Physical Education and Sport, 2022)
This study analyzes the progressive practices at University of Northern Iowa (UNI) against a global sport development model for high performance integrated with healthy lifelong mass participation. The model`s macro-level embraces elements of socioeconomic, cultural, legislative, and organizational support for a sport system by all possible public and private partners and stakeholders. The meso-level includes infrastructure, personnel, and services enabling sport programs, and the micro-level consists of operations, processes, and methodologies for development of individual athletes. The innovative macro-level UNI partnerships mobilized and integrated financial and human resources of private healthcare and public education systems. This includes voluntary community resources in the state of Iowa, creating a meso-level facility, event and educational infrastructures, as well as unique job positions servicing both recovering hospital patients and high performance (HP) athletes competing for Division I National Collegiate Athletic Association (NCAA). At the micro-level, the world`s best methods of clinical rehabilitation and HP science utilize natural outdoor environments, water, gym apparatus, including mobile fitness equipment, and partner resistance for a holistic fitness program with maximum variety and efficient compounded exercises. The holistic fitness program, individualized through isokinetic testing, serves the following purpose: injury prevention; accurate determination of return to play for HP athletes and hospital patients; monitoring athlete and patient progress utilizing strength benchmarks and highlighting strength standards; accurate evaluation of strength and conditioning programming to identify best practices; and the creative integration of strength and conditioning staff and their innovations to benefit the wellbeing and success of athletes, hospital patients, and the community.